An Herbal Formulation of Jiawei Xiaoyao for the Treatment of Functional Dyspepsia: A Multicenter, Randomized, Placebo-Controlled, Clinical Trial. Issue 10 (8th October 2020) - Chen, Guang; Feng, Peimin; Wang, Shaofeng; Ding, Xiangping; Xiong, Jiaying; Wu, Jianhua; Wang, Lihua; Chen, Wei; Chen, Guixia; Han, Mei; Zou, Ting; Li, Lei; et al.
Abstract : INTRODUCTION: To investigate the efficacy and safety of an herbal formulation of Jiawei Xiaoyao (JX) on gastrointestinal symptoms in patients with functional dyspepsia (FD) who had previously rejected standard therapies of proton pump inhibitors, H2 blockers, or Helicobacter pylori eradication. METHODS: A total of 144 adult men and women with FD according to the Rome III criteria were recruited at 9 sites in China from August 2017 to April 2019. Participants were randomized to receive either a JX pill or placebo (12 g/d, 6 g twice a day) for 4 weeks. The primary end point was the change in the total Gastrointestinal Symptom Score (GIS) from baseline to week 4. The secondary end points included the scores on the Hamilton Depression Scale and the Hamilton Anxiety Scale. The safety outcomes included the results of the complete blood count, the liver function test, the renal function test, urinalysis, the fecal occult blood test, and an electrocardiogram. RESULTS: Data from 141 patients (JX pill, n = 70; placebo, n = 71) were statistically analyzed. The mean ± SD of the GIS for the JX pill group at baseline and 4 weeks was 9.3 ± 3.1 and 3.8 ± 3.0, respectively; the mean ± SD of the GIS for the placebo group at baseline and 4 weeks was 9.5 ± 3.4 and 5.3 ± 4.4, respectively (change from baseline to 4 weeks in the JX pill group vs change from baseline in the control group, −1.3 points; P = 0.013). The JX pill group showed greater improvement in both the Hamilton Depression Scale and Hamilton Anxiety Scale scores from baseline to 4 weeks than the placebo group, but the difference was not significant. The total number of adverse events was 30 in the JX pill group vs 20 in the placebo group ( P = 0.240). DISCUSSION: The JX pill was superior to the placebo in terms of improving the GIS in patients with FD but did not significantly improve depression or anxiety symptoms. These findings suggest that the JX pill may have a positive effect on the resolution of gastrointestinal symptoms in patients with FD who are seeking alternative therapies.